Efficient extra‐mitochondrial aerobic ATP synthesis in neuronal membrane systems. Issue 9 (3rd June 2021) - Ravera, Silvia; Bartolucci, Martina; Calzia, Daniela; Morelli, Alessandro M.; Panfoli, Isabella
Abstract: The nervous system displays high energy consumption, apparently not fulfilled by mitochondria, which are underrepresented therein. The oxidative phosphorylation (OxPhos) activity, a mitochondrial process that aerobically provides ATP, has also been reported also in the myelin sheath and the rod outer segment (OS) disks. Thus, commonalities and differences between the extra‐mitochondrial and mitochondrial aerobic metabolism were evaluated in bovine isolated myelin (IM), rod OS, and mitochondria‐enriched fractions (MIT). The subcellular fraction quality and the absence of contamination fractions have been estimated by western blot analysis. Oxygen consumption and ATP synthesis were stimulated by conventional (pyruvate + malate or succinate) and unconventional (NADH) substrates, observing that oxygen consumption and ATP synthesis by IM and rod OS are more efficient than by MIT, in the presence of both kinds of respiratory substrates. Mitochondria did not utilize NADH as a respiring substrate. When ATP synthesis by either sample was assayed in the presence of 10–100 µM ATP in the assay medium, only in IM and OS it was not inhibited, suggesting that the ATP exportation by the mitochondria is limited by extravesicular ATP concentration. Interestingly, IM and OS but not mitochondria appear able to synthesize ATP at a later time with respect to exposure to respiratory substrates, supporting the hypothesis that the proton gradient produced by the electron transport chain is buffered by membrane phospholipids. The putative transfer mode of the OxPhos molecular machinery from mitochondria to the extra‐mitochondrial structures is also discussed, opening new perspectives in the field of neurophysiology. Abstract : Comparison of mitochondrial and extramitochondrial activity in neuronal membrane systems. In the last years, literature reports that the oxidative phosphorylation (OxPhos) machinery is expressed not only on the inner mitochondrial membrane but also on other membranous structures. In order to highlight the similarities and differences between these two entities, in this work, we compared the activity of mitochondrial OxPhos with that expressed in isolated myelin and rod outer segments.